Star apple (Chrysophyllum cainito; Sapotaceae): consumption in five cities of Costa Rica (UNED Research Journal, 2026)
Introduction: There are no studies on the consumption of star apple (Chrysophyllum cainito). Objective: To qualitatively characterize the consumption of star apple in five cities in Costa Rica. Methods: We interviewed 657 persons in San José, Alajuela, Heredia, Cartago, and Liberia, between January and August 2019.  Results:  Liberia had the best knowledge (88% of respondents) and higher consumption (70%) compared to the other cities (73-84% and 47-58%, respectively).  In the five cities, the preference for consumption was reported by 44-68% of women and 49-71% of men, as well as by 13-31% of people aged 15-29, 41-65% of people aged 30-44, 50-88% of people aged 45-59, and 59-100% of people aged 60-99. Most consumed it fresh, once or twice a year and considered it reasonably priced. High-quality star apples were described as slightly soft, uniformly dark purple with intense color, firm with good texture, low in latex, and large.  Conclusion: Large uniform fruits are preferred and Liberia has the highest knowledge and consumption, particularly among older men, but consumption is not frequent and needs better promotion.
Keywords: Central America; fruit; price; consumer; food